2013
DOI: 10.1097/qad.0b013e328360e9fb
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial activation biomarkers increase after HIV-1 acquisition

Abstract: Objective We aimed to determine whether endothelial activation biomarkers increase after HIV-1 acquisition, and whether biomarker levels measured in chronic infection would predict disease progression and death in HIV-1 seroconverters. Design HIV-1-seronegative Kenyan women were monitored monthly for seroconversion, and followed prospectively after HIV-1 acquisition. Methods Plasma levels of angiopoietins-1 and -2 (ANG-1, ANG-2) and soluble vascular cell adhesion marker-1 (VCAM-1), intercellular adhesion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…Endothelial dysfunction is a complication of acute and chronic HIV[35, 36], and markers of endothelial activation (including cellular adhesion molecules, methylarginines, fibrinogen, and D-dimer) have been associated with cardiovascular disease in HIV[34, 37, 39, 40]. Endothelial damage markers have also been associated with COPD in the general population[4246].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is a complication of acute and chronic HIV[35, 36], and markers of endothelial activation (including cellular adhesion molecules, methylarginines, fibrinogen, and D-dimer) have been associated with cardiovascular disease in HIV[34, 37, 39, 40]. Endothelial damage markers have also been associated with COPD in the general population[4246].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examining angiogenic factors in nonpregnant individuals infected with HIV have shown increases in the Ang-2:Ang-1 ratio associated with acute HIV infection, and decreased Ang-1 in chronic disease. 54 In HIV-infected Kenyan women with advanced infection, Ang-2 levels decreased and Ang-1 levels increased following the initiation of ART. 55 On a cellular level, HIV-infected cells release transactivator of transcription, which accumulates on and is taken up by endothelial cells where it acts in synergy with VEGF-A to modify the cytoskeletal structure of endothelium.…”
Section: Commentmentioning
confidence: 99%
“…These adhesion molecules play an essential role in the development of vascular inflammation and endothelial dysfunction [17] which are associated with the pathogenesis of CVD [18]. Although the HIV tat protein induces ICAM and VCAM secretion [19,20], ART regimens suppress both viral load and HIV-induced vascular inflammation, leading to an improvement of endothelial activation and dysfunction [10,21].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between inflammatory pathways and the pathogenesis of HIV, especially the pathogenesis of HIV-related endothelial activation, is not well understood [21]. The interplay between factors associated with CVD and HIV, and the added influence of ART on this relationship is complex and their overall contribution to the vascular system needs further investigation.…”
Section: Introductionmentioning
confidence: 99%